140k views
1 vote
Pls help me with this

Pls help me with this-example-1
User Syntactic
by
5.6k points

1 Answer

6 votes

Answer:

1/(x^(17/12)y^(5/3))

Explanation:

We assume you want to simplify the expression. The applicable rules of exponents are ...

(a^b)(a^c) = a^(b+c)

(a^b)^c = a^(bc)

1/a^b = a^-b

Using these "all at once", we can add up the exponents of each of the variables:

x^(-2/3 -2·0 -(1/2)(3/2))·y^(-2/3-(1/2)·2) = x^(-2/3-3/4)y^(-2/3-1)

= x^(-17/12)y^(-5/3)

=
\frac{1}{x^{(17)/(12)}y^{(5)/(3)}}